Analisis Strategi Optimalisi Market Share Pada Produk Pembiayaan Mudharabah (Studi Kasus BMT Maslahah Cabang Besuk Agung) - Toyyibah, Wardah; Nuntufa; Norhayati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
BMT Maslahah Branch Besuk Agung is still facing several challenges and obstacles in offering mudharabah financing products to its customers. One of the main issues is the low level of public understanding regarding the concept of sharia financing, which often leads to reluctance to utilize the products offered, even though they have pressing financial needs. Therefore, the implementation of effective marketing strategies and customer education becomes crucial to increasing market share. This research focuses on analyzing the factors affecting the low market share of mudharabah financing products and identifying marketing strategies that can be applied to attract more customers. The research methodology employed is a qualitative approach with a case study strategy, where data collection is conducted through in-depth interviews and direct observation at BMT Maslahah Branch Besuk Agung. The findings indicate that enhancing customer awareness of sharia financing products, along with the development of comprehensive educational programs, can significantly drive the growth of the customer base and improve the profitability of the BMT. All proposed marketing strategies are designed to meet customer needs and maximize the positive impact on market share. The BMT also implements innovations in products and services while strengthening relationships with customers through continuous and responsive communication. Therefore, this study provides valuable insights for BMT Maslahah in optimizing the potential of mudharabah financing and expanding access to sharia financial services in the region.